1992
DOI: 10.1007/bf02342444
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular distribution of GLUT 4 in the skeletal muscle of lean type 2 (non-insulin-dependent) diabetic patients in the basal state

Abstract: Insulin resistance of the skeletal muscle is a key feature of Type 2 (non-insulin-dependent) diabetes mellitus. To determine whether a decrease of glucose carrier proteins or an altered subcellular distribution of glucose transporters might contribute to the pathogenesis of the insulin resistant state, we measured glucose transporter numbers in membrane fractions of gastrocnemius muscle of 14 Type 2 diabetic patients and 16 non-diabetic control subjects under basal conditions. Cytochalasin-B binding and immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…Theoretically there could be a decrease in transporter number, an impairment in transporter translocation and/or a decrease in transporter intrinsic activity (26). Conflicting data are available on the reduction of GLUT4 content as a mechanism of glucose transport impairment (19)(20)(21)(22)(23)(24)(25). Therefore, a major role could be played by a reduction in the transporter intrinsic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically there could be a decrease in transporter number, an impairment in transporter translocation and/or a decrease in transporter intrinsic activity (26). Conflicting data are available on the reduction of GLUT4 content as a mechanism of glucose transport impairment (19)(20)(21)(22)(23)(24)(25). Therefore, a major role could be played by a reduction in the transporter intrinsic activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, whole muscle GLUT4 content includes both the functionally active transporters located on the plasma membrane and the transporters located in the intracellular microsomal pool, which do not transport glucose into the cell. The few data available on the GLUT4 content in skeletal muscle plasma membranes of diabetic patients are conflicting, showing either a decrease (24) or no change (25). However, skeletal muscle glucose transport can be regulated not only by changes in the number of glucose transporters located on the plasma membrane, but also by changes in their functional activity (26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly the importance of GLUT4 in the maintenance of glucose homeostasis has been determined. In addition, a defect in its distribution or function has been implicated in the development of type 2 diabetes [82,83]. For example, a 90% impairment of insulin-stimulated GLUT4 translocation to the plasma membrane of skeletal muscle of type 2 diabetic subjects compared with normal controls was demonstrated utilizing a biotinylated photoaffinity label [84].…”
Section: Glut4mentioning
confidence: 99%
“…Recently, two groups have specifically looked at this possibility in human muscle from NIDDM subjects. Whereas Vogt et al [25] found a 40-50% decrease in GLUT4 in their plasma membrane fraction, Lund et al [26] reported no differences in plasma membrane GLUT4 content between muscles of control and diabetic individuals. However, the possibility that GLUT4 is depleted in muscle transverse tubules of diabetic animals or IDDM and NIDDM subjects remains to be investigated.…”
Section: Introductionmentioning
confidence: 95%